Comparison of Cefuroxim versus Cefotaxim in the Treatment of Pneumonia in Children Aged 3 Months- 5 Years an Imaging and Clinical Examination Evidence: Randomized Controlled Trial. - Hashem Mohammed Mansour; Shaban Al Mobayed; Ahmed El Manasra; Rola S. Abudalfa (Medicine Science, 2014)
Pneumonia is a common and potentially serious infection that affects children throughout the world. The aim of this study was to compare between cefuroxim and cefotaxim in the treatment of children with pneumonia. All 3 months-5 years old children admitted from 2/1/2012 to 4/31/2012 at Dorrah Hospital in Gaza were included in this study. The clinical outcome, length of hospital stay, and the association of pneumonia incidence to gender and age were compared. Of the 110 children admitted for non-complicated community acquired pneumonia (CAP), sixty patients were treated with cefuroxime and fifty were treated with cefotaxim. Clinical outcome and length of hospital stay is similar between both groups. Interestingly, the pneumonia incidence is higher in younger children and males. In conclusion, both drugs have similar treatment efficacy in terms of clinical outcome and the length of hospital stay. However, cefuroxim has several advantages over cefotaxim, including (1) oral form, allowing outpatient management, (2) less frequency of administration. Thereby, it should be recommended to treat pneumonia in children. [Med-Science 2014; 3(3.000): 1470-8]